Photon activation method to the investigation of bioobjects content for judicial-biological examination - Dikiy, N.P.; Dyachenko, A.F.; Lyashko, Yu.V.; Medvedeva, E.P.; Uvarov, V.L.; Borovlev, V.I. (Вопросы атомной науки и техники, 2009)
Possibilities of the use of nuclear-physical methods for definition of element composition of biological objects (hair of animals) with the target of receipt of additional evidentiary information at the decision of diagnostics and identification problems within the limits of forensic-biological examination are shown.